Analisis sifat magnetik nanokomposit CoFe2O4/PANi yang disintesis dengan metoda sol-gel (Analysis of the magnetic properties of the CoFe2O4 / PANi nanocomposites synthesized by the sol-gel method) - Rigis Sugianti; - Ramli; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2019)
Cobalt ferrite (CoFe2O4) is a hard magnetic material known for its high coercivity and moderate magnetization, these properties together with great physical and chemical stability, making cobalt ferrite suitable for magnetic sensor applications, magnetic recorders and magnetic sensor building materials. In the field of material, one of the materials that is widely developed today is composite material. CoFe2O4 / PANi nanocomposite was successfully synthesized using the sol-gel method and the growth of CoFe2O4 / PANi nanocomposite layer using spin coating was characterized using X-ray Diffraction to see the size of the Crystal, FTIR test saw the functional group, SEM test to see film thickness. Magnetic properties were analyzed, hysteresis curve obtained remanent magnetization, saturation magnetization and coercivity field. In the experiment there were 5 variations of composition by using CoFe2O4 concentrations in PANi, namely 20%, 30%, 35%, 0%, 50%. Based on XRD data, the crystal size of each concentration is 50.7 nm, 20.3 nm, 33.7 nm, 201.4 nm, 194.4 nm. SEM test is 16.4 nm, 50.8 nm, 128.2 nm, 36.8 nm. VSM test obtained hysteresis curve from the curve then obtained saturation magnetization is 12.10, 6.69, 10.77, 5.78, 3.56 (memu), remanent magnetization is 2.39, 1.54, 2.08, 1.91, 1.22 (memu), the coercivity field is 253.31, 353.80, 312.29, 377.76 (Oe).